A Rasch Analysis of the Tims, Bakker, and Derks (2012) Job Crafting Scale. (November 2019) - Peral, Sergio L.; Geldenhuys, Madelyn
A Rasch validation was performed on the Tims, Bakker, and Derks's Job Crafting Scale (JCS) in the South African working context. The JCS, which has been linked to employee well-being and career-related outcomes, continues to be the most widely used measure of job crafting behavior. Data obtained from the JCS generally showed good fit to the Rasch model. Four items were flagged during the analysis for displaying misfit (1 item) or differential item functioning (3 items), warranting further research attention. The study disclosed the dimensionality of the JCS, the hierarchical ordering and fit of the items, the functionality of the response format, and the ability of the JCS to measure invariantly across men and women, yielding new and interesting insights into the psychometric properties of the scale. The study contributes to research concerning the validity of the JCS in a non-European context, particularly through the use of Rasch analysis as a validation technique.